Perbadingan Hasil Belajar PAI Siswa Antara Menggunakan Model Cooperative Group Investigation Dengan Cooperative Two Stay Two Stray Pada Siswa Kelas X SMK Negeri 1 Ampek Angkek - Rahmi, Asyfida; Monia, Fenny Ayu; J, Januar; Trisno, Bambang (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research is based on the background of the conditions at SMK Negeri 1 Ampek Angkek in class X students, namely the lack of the use of PAI learning models and methods carried out by educators is still less varied. The purpose of this study was to determine the comparison of PAI learning outcomes using the Cooperative Group Investigation model with Cooperative Two Stay Two Stray on Class X Students of SMK Negeri 1 Ampek Angkek. The research used in this study is experimental research with a quantitative approach. The population in this study were all X grade students of SMK Negeri 1 Ampek Angkek which amounted to 278 students. The samples in this study were Fashion 1 class students with 20 students and Fashion 1 with 20 students. The data in this study were collected through tests and analyzed by prerequisite tests and independent sample t tests. Based on the results of the research that has been done, the results show that there is a comparison of students’ PAI learning outcomes between using the GI and TSTS models as evidenced by the results of the independent sample t test, namely the sig value of 0.001 <0.05 and the value of t count> t table, namely 3.568> 2.023. So it can be interpreted that there is a comparison of students' PAI learning outcomes between using the CGI and CTSTS learning models, getting the result that the CTSTS learning model is superior to the CGI learning model so that there is a significant comparison in the learning model that researchers conducted at SMK Negeri 1 Ampek Angkek.